First results from a hidden photon dark matter search in the meV sector using a plane-parabolic mirror system - Knirck, Stefan (Journal of cosmology and astroparticle physics, 2018)
We report on the first results from a new dish antenna search for hidden photon dark matter (HPDM) in the meV mass region. A double mirror system composed of a plane and a parabolic mirror is designed to convert HPDMs into photons focused on a receiver. In this phase 1 experiment we obtain an upper limit on the photon-HP kinetic mixing χ ≲ 10−8 for the mass range of 0.67-0.92 meV using conventional mm-wave technology with a room-temperature receiver and a small-sized mirror system.
Gesehen am 22.11.2019